Earthquake Preparedness for Disabled Students Using the School Watching Approach - Syafruddin Ali Salaka; Iqra S (Indonesian Journal of Global Health Research, 2025)
Mamuju, as one of the cities in West Sulawesi, Indonesia, is highly prone to earthquakes. Recently, on January 15, 2021, Mamuju was struck by a major earthquake with a magnitude of 6.2, accompanied by hundreds of aftershocks. The disabled community, particularly students in Special Schools (SLB), faces unique challenges during disasters. Various physical, sensory, or cognitive limitations necessitate a tailored approach to disaster preparedness education. The School Watching approach can enhance awareness and collaboration among stakeholders, including local governments, educational institutions, and organizations focused on disability issues. Objective to improve earthquake preparedness among disabled students at SLB Mamuju through the implementation of the School Watching approach, aiming to create an inclusive, adaptive, and resilient school environment in disaster situations. This study is a quantitative research with a quasi-experimental design, using a pretest and posttest control group approach, conducted from May to July 2024. The study population consisted of SLB students in Mamuju Regency, with a total of 40 respondents divided into two groups using the total sampling technique. The intervention group of 20 students received disaster preparedness education and the School Watching approach for earthquake preparedness twice, each session lasting 60 minutes. The control group was only provided with earthquake preparedness material for 60 minutes without the School Watching approach. Before delivering the material, an initial measurement was conducted to evaluate the students' preparedness and knowledge related to earthquakes, as well as after the material delivery. Descriptive statistical tests were used to summarize the characteristics of the respondents and the pre-test and post-test scores. Subsequently, paired t-tests were conducted to compare the pre-test and post-test results. The School Watching approach had a significant impact on disaster preparedness among disabled students at SLB Mamuju. This was demonstrated by a significant difference between the intervention group and the control group. The School Watching program proved effective in improving earthquake preparedness among disabled students. This is evidenced by a significant difference in the pre-test and post-test results of the intervention group compared to the control group.